2007
DOI: 10.1242/dev.005447
|View full text |Cite
|
Sign up to set email alerts
|

Divergent roles of ApoER2 and Vldlr in the migration of cortical neurons

Abstract: Reelin, its lipoprotein receptors [very low density lipoprotein receptor (Vldlr) and apolipoprotein E receptor 2 (ApoER2; also known as Lrp8)], and the cytoplasmic adaptor protein disabled 1 (Dab1) are important for the correct formation of layers in the cerebral cortex. Reeler mice lacking the reelin protein show altered radial neuronal migration resulting in an inversion of cortical layers. ApoER2 Vldlr double-knockout mutants and Dab1 mutants show a reeler-like phenotype, whereas milder phenotypes are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(163 citation statements)
references
References 50 publications
8
151
0
2
Order By: Relevance
“…We observed strong clustering of ApoER2 by Fc-RAP, suggesting that our assay was sensitive for detecting regulated receptor clustering. We next tested F-spondin and Reelin, both of which bind to ApoER2 (11,12,19) and are important in embryonic development (2,5,6,13). Both F-spondin and Reelin induced clustering of ApoER2, a potential signaling mechanism related to the function of these molecules in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed strong clustering of ApoER2 by Fc-RAP, suggesting that our assay was sensitive for detecting regulated receptor clustering. We next tested F-spondin and Reelin, both of which bind to ApoER2 (11,12,19) and are important in embryonic development (2,5,6,13). Both F-spondin and Reelin induced clustering of ApoER2, a potential signaling mechanism related to the function of these molecules in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…ApoER2 knockout mice showed that early layers of cortex were formed normally, whereas the formation of superficial late layers was affected severely. These data suggest that ApoER2 signaling plays a role in the formation of late generation neurons (5). VLDLR knockout mice showed neurons migrating in the marginal zone, suggesting that VLDLR may act as a stop signal for migrating neurons (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During embryonic corticogenesis, Cajal-Retzius cells orchestrate the typical inside-out layering of the cortex by releasing the glycoprotein reelin, which is critical for neuronal migration and cell positioning by activating the very-low-density lipoprotein (VLDL) receptor and the apolipoprotein E receptor 2 (ApoER2) (1)(2)(3)(4)(5)(6). In vivo, reelin is cleaved by extracellular metalloproteinases into three fragments of which only the central fragment R3-6 is able to bind to the ApoER2 and VLDL receptors (7)(8)(9).…”
Section: -Ht3 Receptor ͉ Cajal-retzius Cells ͉ Postnatal Developmentmentioning
confidence: 99%
“…VLDLR and ApoER2 are thought to act in a similar fashion since both receptors are able to activate the Reelin signaling cascade. However, recent studies pointed to divergent functions of ApoER2 and VLDLR in the migration of cortical neurons during brain development (Hack et al, 2007).…”
Section: Introductionmentioning
confidence: 99%